Cardiothoracic surgery training in South Africa: Where to from here? - Rossouw, Gawie; Janson, Jacques (SA Heart Journal, 2017)
Standing in the operating theatre and seeing a heart’s function improve after replacing a stenotic aortic valve, or repairing an incompentent mitral valve or revascularising obstructed coronary arteries is an amazing experience. Very few people have the oppurtunity to see a heart come to life when we remove the aortic cross clamp after cardiac surgery. Blood fl ushes the cardioplegia out of the coronaries, the myocardial cells fuel its sodium, potassium and calcium pumps from the life giving blood, and the heart starts beating: a miracle we get to witness every day.